2017
DOI: 10.1186/s12864-017-3829-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic dynamics in soybean near-isogenic lines differing in alleles for an aphid resistance gene, following infestation by soybean aphid biotype 2

Abstract: BackgroundGenetic resistance of soybean [Glycine max (L.) Merr] against Aphis glycines provides effective management of this invasive pest, though the underlying molecular mechanisms are largely unknown. This study aimed to investigate genome-wide changes in gene expressions of soybean near-isogenic lines (NILs) either with the Rag5 allele for resistance or the rag5 allele for susceptibility to the aphid following infestation with soybean aphid biotype 2.ResultsThe resistant (R)-NIL responded more rapidly to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 57 publications
4
27
0
Order By: Relevance
“…This outcome was not surprising and has been reported previously. For example, Lee et al [ 37 ] found higher number of DEGs in resistant soybean in response to soybean aphid, Aphis glycines Matsumura (Hemiptera: Aphididae) in comparison to an aphid-susceptible soybean line.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This outcome was not surprising and has been reported previously. For example, Lee et al [ 37 ] found higher number of DEGs in resistant soybean in response to soybean aphid, Aphis glycines Matsumura (Hemiptera: Aphididae) in comparison to an aphid-susceptible soybean line.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…3 ). On the other hand, genes involved in detoxification, which is one of the defenses linked to plant response to aphid herbivory [ 37 , 45 , 46 ] was up-regulated in both 2- and 6-wk resistant genotype and in the 2-wk susceptible genotype (Fig. 3a, b and c ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another enriched pathway in the resistant cultivar was photosynthesis. Previous transcriptomic study on soybean near-isogenic lines differing in alleles for an aphid resistance gene, Rag5 following infestation by soybean aphid biotype 2 has shown DEGs enriched for photosynthesis [71]. Physiologically, photosynthesis rates have been reduced up to 50% on soybean aphid infested leaflets [72].…”
Section: Discussionmentioning
confidence: 99%